Effect of Teaching Intervention on Cancer Facts to Reduce Cancer Social Stigma in Rural Adults-A Pilot Study - Rose Mary Mathew; Shambhavi; Sandra Maria Sibi (Journal of Clinical and Diagnostic Research, 2021)
Introduction: Worldwide, cancer is the second major cause of death and is accountable for an approximately 9.6 million deaths in the year 2018. Cancer carries a stigma due to its link with death. This affects the health seeking behaviour of the cancer patients. Aim: To evaluate the effect of teaching intervention on cancer facts to reduce social stigma among rural adults. Materials and Methods: This quasi-experimental pretest posttest control group study was conducted from 5th January 2021 to 5th February 2021, in rural community at Mangalore, Karnataka, India. Hundred adults between 18-65 years of age were selected based on purposive sampling technique and randomly assigned to an experimental and control group. Data was collected using baseline proforma and self-designed cancer social stigma scale which is a 5-point rating scale, consisting of 20 statements. The total score of each participant was calculated and categorised as severe, moderate, mild and no social stigma. Individual teaching intervention was given on first day to the intervention group and post-test was conducted after seven days on both the groups. The data were analysed using the t-test and chisquare tests. Results: The total study population of 100 adults was divided into intervention group (mean age 33.34±4.46 years) and control group (mean age 36.22±4.07 years) of 50 subjects each. Before the teaching intervention, the mean and Standard Deviation (SD) of social stigma scores of intervention group and control group were 59.9±13.6 and 61.38±9.8, respectively. After the intervention, the score of the intervention group and control group were 30.62±4.5 and 61.44±10.8, respectively. Independent t-test showed that there was a significant difference in social stigma score between intervention group and control group after the intervention (p-value<0.05). Conclusion: Study findings revealed that teaching intervention on cancer fact is effective in reducing social stigma among general population. Since the prevalence of cancer is high, there is an immediate need to educate the rural population on prevention, myths and realities of cancer.